Fixed point approach to the stability of an integral equation in the sense of Ulam-Hyers-Rassias - Akkouchi, Mohamed; Bounabat, Abdellah; Rhali, M.H. Lalaoui (Annales Mathematicae Silesianae, 2011)
In this paper, by using the classical Banach contraction principle, we investigate and establish the stability in the sense of Ulam–Hyers and in the sense of Ulam–Hyers–Rassias for the integral equation which defines the mild solutions of an abstract Cauchy problem in Banach spaces.